Reverse Engineering Blok Silinder, Comp-Head Genset X dan Pengaruh Developer terhadap Hasil 3D Scanning - Muhammad Muhammad; Yusmira Herwan (Journal of Mechanical Engineering and Mechatronics, 2016)
Reverse engineering is a process in manufacturing, which aims to reproduce or recreate an existing model either component, sub-assembly, or product without using the data document design or picture of the existing work. Reverse engineering on the cylinder block and com.head conducted to determine the actual size and shape of the part is to create a 3D surface or solid using Geomagic software design x based stl-file of the 3D scanning using ATOS II. Critical part of this part is located in the combustion chamber and the position of head hole, so the tolerance used is ± 0.03 mm. By testing the differences between type A developer using the addition of an average dimension of 2 – 8 mm. With the addition of developer type B average dimension of 4 – 14 mm. While the difference between type A and type B by a margin dimensions of ± 0 – 11 mm, which developer A can affect the size of the work piece is better than the developer B.Keywords. Reverse Engineering, Developer, Cylinder block, CAE, CAM.